Chlorophyll derivatives/MXene hybrids for photocatalytic hydrogen evolution: Dependence of performance on the central coordinating metals. (19th January 2022) - Li, Yuanlin; Zheng, Tianfang; Liu, Yanxiang; Dall'Agnese, Yohan; Dall'Agnese, Chunxiang; Liu, Cheng-Liang; Sasaki, Shin-ichi; Tamiaki, Hitoshi; Wang, Xiao-Feng
Abstract: Development of efficient photocatalytic hydrogen evolution reaction (HER) with illumination of visible light is challenging. In this work, five chlorophyll derivatives (M-Chls; M = H2 /Cu/Ni/Co/Zn) with different central ions in its cyclic tetrapyrrole ring including free base, copper, nickel, cobalt, and zinc were synthesized and employed as the effective visible-light harvester for efficient HER. In addition, two-dimensional (2D) noble metal-free co-catalyst Ti3 C2 T x MXene was used as an excellent electron capturer due to its outstanding conductivity property. These M-Chls are modified on the surface of Ti3 C2 T x MXene with 2D accordion-like morphology by means of a simple deposition process to form noble metal-free Chl/Ti3 C2 T x -based photocatalysts for HER. It is found that the best HER performance as high as 49 μmol/h/gcat was achieved with the Co-Chl@Ti3 C2 T x hybrid, which was much higher than those of other M-Chl@Ti3 C2 T x composites. This research provides a specific way to synthesize low-cost and environmentally friendly natural Chls for developing highly efficient photocatalytic HER through molecular engineering. Graphical abstract: Image 1 Highlights: Chl- a derivatives M-Chls with five different central ions, were used for HER. Noble metal-free photocatalytic system of M-Chls@Ti3 C2 T x hybrid is developed. This work provides a way to synthesize environmentally friendly Chls for HER.